2019
DOI: 10.1097/md.0000000000014492
|View full text |Cite
|
Sign up to set email alerts
|

Acute cholecystitis as a rare and overlooked complication in stroke patients

Abstract: Acute cholecystitis (AC) is a rare but possible medical complication found in stroke patients. As many stroke patients present with neurologic symptoms, such as altered mental status, motor weakness, global aphasia, or dysarthria, clinical symptoms and signs of AC are often unexpressed or overlooked. As a result, the diagnosis of AC is often delayed with subsequent secondary complications in these stroke patients. This study aims to evaluate the clinical incidence, manifestations, and predictive factors of AC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…It has been suggested that cerebrovascular disease is a risk factor in the pathogenesis of AAC [ 63 , 64 ], but there is not enough evidence in medical literature regarding this subject.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that cerebrovascular disease is a risk factor in the pathogenesis of AAC [ 63 , 64 ], but there is not enough evidence in medical literature regarding this subject.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] Notably, case studies have surfaced, demonstrating instances wherein individuals afflicted with hypertrophic obstructive cardiomyopathy, accompanied by cholecystitis, encountered complete atrioventricular block, a phenomenon attributable to the cardio-biliary reflex, thereby positioning cholecystitis as an infrequent but notable cause of complete atrioventricular block. [12] The research conducted by Yoo et al [13] revealed that acute cholecystitis complications frequently emerge in patients suffering from cerebral infarction. Nevertheless, the pervasiveness of neurological manifestations in patients with stroke, such as altered mental status, motor weakness, global aphasia, or dysarthria, often results in underrepresentation or overshadowing of clinical symptoms indicative of cholecystitis.…”
Section: Introductionmentioning
confidence: 99%
“…This condition is a common cause of hospital admission and contributes to 3%−10% of all cases of abdominal pain 18 . In nearly 95% of cases, cholecystitis is associated with cholelithiasis 19 …”
Section: Introductionmentioning
confidence: 99%
“…18 In nearly 95% of cases, cholecystitis is associated with cholelithiasis. 19 Cholecystitis is a multi-etiology pathology with a wide range of sonographic presentations, which can be primarily divided into calculous and acalculous forms. 20 The primary diagnostic criterion for sonography is the presence of the sonographic Murphy sign in association with gallstones.…”
Section: Introductionmentioning
confidence: 99%